Quando o mel é bom a abelha sempre volta: um estudo etnográfico no aglomerado do mel na fronteira Sant'ana do Livramento/Brasil e Rivera/Uruguai - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This study aims to characterize the culture of the honey cluster on the border of Sant'ana do Livramento-Brasil and Rivera-Uruguay. The present study was carried out by me beekeeper during the year 2019 until January 2021 in the honey cluster of Fronteira, and as a method has an ethnography that is the experience of the research field by the researcher of the study. The data collection of the study was carried out by means of semi-structured changes, analyzed and non-participating participants such as those who took part in the field, photographs, videos and informal conversations with beekeepers in the honey cluster. Collecting the data collection, the distance from the field, which is the practice of ethnography, was carried out, and an analysis of the data was performed using the content analysis technique. As a result of this study, the honey cluster at Fronteira is still little publicized, there is a Santanense Beekeepers Association (ASA), which is part of this cluster, however, the cluster is not concentrated only within the ASA, but rather by several closed groups of beekeepers spread across the Fronteira Sant'ana do Livramento-Brasil and Rivera-Uruguay. It is relevant that beekeeping is an activity of historical and cultural promotion, part of the time it is a bond of family dependence passed on in the family, and that this activity most of the time serves as a supplement of income because the majority of beekeepers in the Fronteira exercised beekeeping as a second profession or as a hobby.
When honey is good the bee always comes back: an ethnographic study in the honey cluster on the Sant'ana do Livramento/ Brazil and Rivera /Uruguay border
Keywords: Mel; Apicultura; Cadeia de produção; Honey; Cluster; CNPQ::CIENCIAS SOCIAIS APLICADAS